Bachelor of Computer Science with Honours (Information Systems) - Universiti Malaysia Sarawak, Faculty of Computer Science and Information Technology (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Sijil Sarjana Muda Fakulti Sains Komputer dan Teknologi Maklumat 2022 bagi 64 orang pelajar.